2016
DOI: 10.1097/acm.0000000000001284
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Women Faculty’s Preferences Regarding Mentor Similarity: A Multi-Institution Study in Academic Medicine

Abstract: Purpose To investigate which mentor similarity characteristics women faculty in academic medicine rate most important and to determine whether the importance of similarity differs among women faculty based on current and prior mentoring, demographic and personal factors, and career factors. Method Cross-sectional survey data from 3,100 women faculty at 13 purposively sampled U.S. medical schools were collected in 2012. The preferences of participants regarding the importance of mentor similarity in terms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 53 publications
1
48
0
Order By: Relevance
“…Mentorship programmes are also essential for career advancement. Yet, women face greater barriers in accessing mentors, with one recent study citing that 34% of female faculty lack a current mentor and over 10% have never had a mentor 34. Institutions can improve gender equity by developing mentorship programmes for women, with a focus on scholarship and leadership 35.…”
Section: Discussionmentioning
confidence: 99%
“…Mentorship programmes are also essential for career advancement. Yet, women face greater barriers in accessing mentors, with one recent study citing that 34% of female faculty lack a current mentor and over 10% have never had a mentor 34. Institutions can improve gender equity by developing mentorship programmes for women, with a focus on scholarship and leadership 35.…”
Section: Discussionmentioning
confidence: 99%
“…Women represent approximately half of students entering medical schools and more than half of those entering PhD programs, yet a collection of articles in this issue 18 suggest that women continue to confront career barriers unbeknownst to many of their men counterparts in academic medicine. Women continue to be paid lower salaries, receive less funding, have less opportunity to publish, and be promoted at slower and lower rates.…”
mentioning
confidence: 99%
“…Indeed, insufficient mentoring is a significant barrier to advancement of women within the academic pipeline 15,16 . There are many advantages derived from a productive mentoring relationship: faculty members with mentors publish at a greater frequency, receive more promotions, and have heightened fulfilment over the course of their career 17 .…”
Section: Access To Mentorshipmentioning
confidence: 99%
“…Therefore, Carapinha et al determined which characteristics were most important to women in academic medicine when choosing a mentor. 17 Also, they examined whether or not interests varied by race, academic rank, or demographic areas 17 . A survey of women faculty members at 13 medical schools nationwide indicated that women reported that the strongest preference for having a mentor within the same department or institution; however, this was less true for more senior faculty.…”
Section: Access To Mentorshipmentioning
confidence: 99%
See 1 more Smart Citation